A comparative and experimental study on performances of Natural gas-Air Combustion, Helium, and Air as Propellants in a Gas Gun. Issue 4 (12th March 2022) - Zarei, SH.; Majzoobi, GH.; Ahmadi Kia, H.
ABSTRACT: In this study, the performance of a single-stage gas gun with a natural gas-air mixture as the propellant gas is investigated by measuring the explosion pressure and the projectile velocity. In this work, the combined effect of elevated initial pressure, mixing, equivalence ratio, and ignition energy on the explosion pressure and projectile velocity is studied. To assess the performance of the natural gas-air combustion, a series of tests with helium and air as the propellant gas are carried out to measure the projectile velocity. The fuel used in this study consisted of 84.2% methane, 9.5% ethane, and 3.7% propane. The helium gas was 99.999% pure. The volume fraction of fuel in the natural gas-air mixture varied between 4.98% and 17.3%, and the flammability limits of the natural gas were between 4.41% and 14.47%. The equivalence ratio Φ was used to control the fuel concentration in the mixture. The equivalence ratio in this study was 0.5, 0.75, 1, 1.5, and 2. The experimental results indicated that despite the low percentage of methane and high percentage of higher hydrocarbons in natural gas, the maximum pressure still occurs at the equivalence ratio 1, the finding which had already been proved to be the case for pure methane. However, the maximum combustion pressure is reduced compared to other fuels with higher methane and lower hydrocarbon content. Also, the study showed that the maximum combustion pressure increased with rising the ignition energy also when the mixer was used to blend the natural gas-air mixture. The experimental results showed that at low pressures, the projectile velocity was higher using helium compared to the same pressures produced by the combustion of methane-air mixture. However, at higher pressures, the projectile velocity was much higher for the pressures produced by combustion due to its lower molecular weight and the heat produced in the combustion process. The price analysis also indicated that for the same output pressure, the cost of a test with a methane-air explosion is 78 times lower than that of a test with helium.